A new hope to control foodborne diseases and pollution: potential antimicrobial activity of banana (Musa paradisiaca) peels against food borne pathogenic microbes - Ahmed, Qamar Uddin; Helal Uddin, A.B.M.; Khan Chowdhury, Ahmed Jalal (2014)
In food industries, different kinds of antimicrobial agents are used during food processing in order to prevent and controlling diseases, enhance the growth and also to increase the production efficiency. However, their persistent use leads to the emergence of resistant in microorganism. Thus, alternative strategies are sought by using unutilized and safe antimicrobial byproducts from natural resources. Musa paradisiaca L. (banana) peels are usually treated as wastes and are discarded during the processing and are responsible for increased pollution. Hence, this study was designed to explore the antimicrobial potential of peels extracts of Musa paradisiaca in order to generate safe and cheap antimicrobials as well as to address issues related to pollution due to such wastes. Ethanol, dichloromethane and aqueous extracts from two different varieties of M. paradisiaca, i.e., Nangka (M. paradisiaca variety Nangka) and Tanduk (M. paradisiaca variety Tanduk) peels against eight (8) pathogenic bacteria (Bacillus cereus, Escherichia coli, Pseudomonas aeruginosa, Enterococcus faecalis, Staphylococcus aureus, Burkholderiacepacia, Vibrio alginolyticus, and Vibrio parahaemolyticus) and three (3) fungal species (Candida albicans, Candida tropicalis and Candida krusei) using disc diffusion and broth micro-dilution methods. The best activity by disc diffusion method for bacteria was demonstrated by ethanolic extract of Tanduk peel against S. aureus with average inhibition zones of 30 mm while the best activity for fungi showed by dichloromethane extract of Tanduk peel against C. krusei with average inhibition zones of 10 mm. However, based on this method, the least active bacteria was found to be V. parahaemolyticus since it was resistant to most of the extracts whereby for fungi, C. albicans was the least active. Moreover, the minimum inhibitory concentration (MIC) results showed that all extracts inhibited the growth of tested microorganisms in the range of 6.25 to 100 mg/mL. Among the extracts, ethanolic extract of Tanduk peel exhibited lowest MIC and minimum bactericidal concentration (MBC) values against B. cepacia at 6.25 mg/mL whereas for fungi, dichloromethane extract of Tanduk peel exhibited lowest MIC and minimum fungicidal concentration (MFC) values against C. albicans at 25 mg/mL. The results of MBC or MFC also showed that some extracts were bactericidal or fungicidal against certain microorganisms while others were bacteriostatic or fungistatic. It is concluded from this study that ethanol extract of Tanduk peel exhibited the most potent antimicrobial activity. Therefore, the extracts of M. paradisiaca L. peel waste could be potential source as antimicrobial alternatives and may be effective to utilize as a natural source of antimicrobial agent in pharmaceutical industries.